The problem of causality in Islamic thought : a viewpoint of Al-Ghazali / Khalid Ismail - Ismail, Khalid (Universiti Teknologi MARA, Perlis, 2006)
The problem of causality (al-Sababiyyah) is one of the most controversial issues in Islamic theology in particular and philosophy in general. It discusses cause and effect such as fire is the cause of burning, marriage is the cause of having children, medicine is the cause of health and so on. In this modest paper, the author shall attempt to explain and analyse two essential groups in the history of Islamic Thought namely the Muslim Theologians (al- Mutakallimun) and Muslim Aristotelian Philosophers (al-Falasifah al- Masya 'iyyun). The former have usually used the term al-Sabab whereas the latter employed the term al-Ilah in referring to the theory of causality.